Gray Matter Volume and Cognitive Performance During Normal Aging. A Voxel-Based Morphometry Study - Ramanoël, Stephen; Hoyau, Elena; Kauffmann, Louise; Renard, Félix; Pichat, Cédric; Boudiaf, Naïla; Krainik, Alexandre; Jaillard, Assia; Baciu, Monica (Frontiers in Aging Neuroscience, 2018)
Normal aging is characterized by decline in cognitive functioning in conjunction with extensive grey matter (GM) atrophy. A first aim of this study was to determine GM volume differences related to aging by comparing two groups of participants, middle-aged (MAG, mean age 41 years, N=16) and older adults (OG, mean age 71 years, N=14) who underwent an MRI voxel-based morphometry (VBM) evaluation. The VBM analyses included two optimized pipelines, for the cortex and for the cerebellum. Participants were also evaluated on a wide range of cognitive tests assessing both domain-general and language-specific processes, in order to examine how GM volume differences between OG and MAG relate to cognitive performance. Our results show smaller bilateral GM volume in the OG relative to the MAG, in several cerebral and right cerebellar regions involved in language and executive functions. Importantly, our results also revealed smaller GM volume in the right cerebellum in OG relative to MAG, supporting the idea of a complex cognitive role for this structure. This study provides a broad picture of cerebral, but also cerebellar, and cognitive changes associated with normal aging.